On general characterization of Young measures associated with Borel functions - Grzybowski, Andrzej Z.; Puchała, Piotr (Archives of Control Sciences, 2026)
We prove that the Young measure associated with a Borel function f is a probability distribution of the random variable f(U), where U has a uniform distribution on the domain of f. Examples of specific applications of the main result, including Monte Carlo method of simulation of Young measures, are presented with comments.